Classroom Action Research on Implementing the Constructive Collaborative Problem-Based Learning (PBL) Method for Developing Character Education through Prophets' Stories among Fifth Graders at SD-2 YPK Bontang - Hikmat Abdurochman (Tasqif: Journal of Islamic Pedagogy, 2024)
The issue of student morals/character in the world of education remains a central concern for all school members, especially teachers who directly educate them. One instance occurred in class 5A at SD-2 YPK Bontang, where most students appeared bored in learning, impatient, unfocused, not serious, hesitant to make decisions in determining solutions, and lacked self-confidence. The aim of this research was to investigate the implementation of the constructive collaborative method using the Problem-Based Learning (PBL) model in Islamic Education learning with material on the stories of the Prophets in improving student character. The research methodology employed was Classroom Action Research (CAR), focused on classroom situations, with a qualitative research approach. This study was conducted over two cycles, with each cycle having research stages including planning, acting, observing, and reflecting. The research subjects were 5A grade students at SD-2 YPK Bontang, consisting of 6 boys and 6 girls with varying learning abilities and life backgrounds. The data collection techniques used were tests, observations, and documentation. The data sources came from several sources, including informants such as the 5A grade teacher and students at SD-2 YPK Bontang, learning archives and documents, learning observation results, and learning outcome tests. The data analysis technique used was descriptive. The results showed a significant increase in the class average score from 75.9 in cycle 1 to 91.5 in cycle 2. The percentage of students achieving the minimum mastery criteria also increased significantly from 50% in cycle 1 to 100% in cycle 2. Based on the discussion of the data, it can be concluded that the use of the constructive collaborative method with the Problem-Based Learning (PBL) model can improve the attitudes and character of 5th-grade students in the material on the exemplary stories of the prophets and messengers at SD-2 YPK Bontang.